2001
DOI: 10.1002/path.874
|View full text |Cite
|
Sign up to set email alerts
|

DNA image cytometry and human papillomavirus (HPV) detection help to select smears at high risk of high-grade cervical lesions

Abstract: Three samples were submitted from women undergoing routine screening (n=910): two smears (one for routine cytology and one for DNA image cytometry) and a scrape for human papillomavirus (HPV) testing. DNA histograms were classified as suspect in cases of aneuploidy, polyploidy, and/or diploidy with a high proliferation rate. Follow-up was available in 239 cases. The primary end-point was the presence of a high-grade squamous intraepithelial lesion (HGSIL) at biopsy. Seventy women (7.7%) had a high-risk (HR) HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…This suggests that detection of 3q gain could be more sensitive than measurement of the nuclear DNA content alone. 10,37,38 The interpretation of the hybridization patterns provides evidence that chromosomal instability, measured in this study as the variability of hybridization patterns among cells in a given case, increases with the grade of dysplasia as well. This suggests that early chromosomal aneuploidies can develop in an otherwise genomically stable nucleus, and that the acquisition of specific chromosomal imbalances (in cervical carcinomas the gain of 3q) coincides with the HPV-mediated compromise of TP53 and RB1 function to promote tumorigenesis and eventually the acquisition of crude nuclear aneuploidy that is present in most invasive cervical carcinomas.…”
Section: Discussionmentioning
confidence: 68%
“…This suggests that detection of 3q gain could be more sensitive than measurement of the nuclear DNA content alone. 10,37,38 The interpretation of the hybridization patterns provides evidence that chromosomal instability, measured in this study as the variability of hybridization patterns among cells in a given case, increases with the grade of dysplasia as well. This suggests that early chromosomal aneuploidies can develop in an otherwise genomically stable nucleus, and that the acquisition of specific chromosomal imbalances (in cervical carcinomas the gain of 3q) coincides with the HPV-mediated compromise of TP53 and RB1 function to promote tumorigenesis and eventually the acquisition of crude nuclear aneuploidy that is present in most invasive cervical carcinomas.…”
Section: Discussionmentioning
confidence: 68%
“…It is well known that cervical lesions in which cells have an aneuploid DNA profile are more likely to persist or progress than those with diploid or polyploid profiles (17)(18)(19)(20). Lorenzato and colleagues (21) reported that flow cytometric DNA ploidy measurement on conventional cervical smears positive for HPV could help detect women at high risk of cervical cancer. To our knowledge, there is limited data on DNA cytometry testing as a stand-alone screening test…”
mentioning
confidence: 99%
“…10,27,28 Since 2001, the International Consensus Conference on the Fight Against Cervical Cancer International Academy of Cytology (IAC) has recommended DNA image cytometry as a useful adjunct method for identifying cervical intraepithelial lesions with a high risk of progression.…”
Section: Discussionmentioning
confidence: 99%
“…These abnormalities are linked to or are the consequence of chromosomal instability induced by the presence of HR-HPV, and are associated with DNA ploidy disturbances. 7,[8][9][10][11] DNA aneuploidy indicates a potential neoplastic development toward cervical dysplasia. 9,12,13 Several mechanisms for DNA ploidy abnormalities in cervical lesions have been described, in particular the HR-HPV E7 oncoprotein expression, which blocks cell differentiation and induces DNA synthesis 14 by interacting with tumor suppressor pRB.…”
mentioning
confidence: 99%